2015
DOI: 10.1088/2053-1583/2/1/011003
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the optical and electrical properties of graphene ink thin films by laser-annealing

Abstract: We demonstrate a facile fabrication technique for graphene-based transparent conductive films. Highly flat and uniform graphene films are obtained through the incorporation of an efficient laser annealing technique with one-time drop casting of high-concentration graphene ink. The resulting thin films are uniform and exhibit a transparency of more than 85% at 550 nm and a sheet resistance of about 30 kΩ/□. These values constitute an increase of 45% in transparency, a reduction of surface roughness by a factor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 21 publications
2
15
0
1
Order By: Relevance
“…These include the dispersion of 2DMs directly in solvents like NMP or DMF without binder,[61a,170b] and the use of binders as viscosity modifiers and stabilizers. Commonly selected binders include EC[58–60,61b,173] and ethylene glycol. [61a,62,170a] However, UILPE in high boiling point solvents is unsuitable for printing due to its low viscosity and limited ink concentration.…”
Section: Patterning Of 2d Inks Into Functional Structures For Electromentioning
confidence: 99%
“…These include the dispersion of 2DMs directly in solvents like NMP or DMF without binder,[61a,170b] and the use of binders as viscosity modifiers and stabilizers. Commonly selected binders include EC[58–60,61b,173] and ethylene glycol. [61a,62,170a] However, UILPE in high boiling point solvents is unsuitable for printing due to its low viscosity and limited ink concentration.…”
Section: Patterning Of 2d Inks Into Functional Structures For Electromentioning
confidence: 99%
“…The increase in the conductivity of such fi lms after laser annealing is related to the reduction of the structural disorder as confi rmed with the help of Raman spectroscopy. [ 64 ] Simulations of temperature dynamics after laser irradiation were also studied in our works. The transient temperature distribution in GO fi lms was simulated using pulsed laser irradiation (t = 10 ps) with a wavelength of 1064 nm and a Gaussian temporal beam profi le applying the software COMSOL Multiphysics, and the results are presented in Figure 10 .…”
Section: Film Structuring and Patterningmentioning
confidence: 99%
“…Del and co-workers [ 64 ] attempted to adjust graphene ink for electronic applications such as transparent electrostatic dissipation, by laser annealing the graphene fi lms. They employed a CW laser (532 nm) to optimize the optical and electronic properties of such graphene ink thin fi lms.…”
Section: Devicesmentioning
confidence: 99%
“…Secor and co-workers proposed a graphene ink-nitrocellulose electrochemical sensor for H 2 O 2 determination [33]. Several works have demonstrated that a post treatment of the graphene ink could improve its conductivity through thermal reduction process [12,34,35]. More specifically, Arapov et al [12], Secor et al [34], and Del et al [35] enhanced graphene ink films to sheet resistances of 1.4 Ω/cm, 21.4 Ω/cm, and 30 kΩ/cm, respectively.…”
Section: Introductionmentioning
confidence: 99%